Meat fatty acids profile including metabolic, qualitative, nutritional indices, and organoleptic evaluation as affected by Rumex nervosus leaves meal fortified broiler diets - Mohammed M. Qaid; Saud I. Al-Mufarrej; Maged A. Al-Garadi; Abdulaziz A. Al-Abdullatif; Abdulmohsen H. Alqhtani; Rashed A. Alhotan; Abdulrahman S. Alharthi; Abdulgader Y. BaZeyad (Italian Journal of Animal Science)
The effects of dietary supplementation with Rumex nervosus leaves (RNL) on fatty acid (FAs) indices, organoleptic evaluation, performance index, and feed efficiency were investigated. This study consists of five treatments. Broilers in treatments 1–4 received basal feed plus RNL at doses of 0, 1, 3, and 5 g/kg, while broilers in treatment 5 received basal feed plus the antibiotic Colimex. On day 34, FAs profile and organoleptic assessment were evaluated, and performance index and feed efficiency were determined for the entire experimental period. Results showed that FAs profile of the breast meat was affected by treatments with varying degrees (p˂0.05). The 1 g RNL resulted in the highest eicosapentaenoic acid + docosahexaenoic acid, which resulted in the highest meat lipid quality, the highest elongation index, improved organoleptic characteristics, and tended to improve performance index, feed efficiency, and nutritional index. The 5 g RNL treatment reduced total saturated fatty acids (ƩSFAs), omega-6/omega-3 ratio, especially linoleic acid/α-linolenic acid ratio, alanine aminotransferase, and increased total omega-3 fatty acids, unsaturation index, and Δ9-desaturase. In conclusion, RNL can be introduced to broiler diets, especially at an incorporation rate of 1 g, and it promotes broiler health and performance because it contains phytoconstituents that can alter the content and indices of FAs meat and improve storability and sensory quality.